2022
DOI: 10.1227/neu.0000000000002314
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Synovial Cysts—Should You Fuse or Not?

Abstract: BACKGROUND:Spinal synovial cysts are lesions that most commonly occur in the lumbar region. The need for an instrumented spinal fusion in addition to lumbar decompression with removal of the synovial cyst is unknown.OBJECTIVE:To test the hypothesis that select patients who underwent decompression with instrumented fusion for lumbar synovial cysts would be less likely to have subsequent surgery (SS) in a 2-year period than patients treated with laminectomy alone.METHODS:This retrospective cohort study was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Five studies showed that patients with LSC/Stenosis undergoing primary decompressions/fusions resulted in lower LSC recurrence rates vs. for those having decompressions alone [Table 1]. [1,7,9,14,16] 1]. [4] Notably, preoperative LSC were located at the same level of DS (42.5%), and this correlated with facet arthropathy (89.3%), and degenerative disc disease (48.8%).…”
Section: Lsc/lumbar Stenosis Treated With Primary Decompressions/fusi...mentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies showed that patients with LSC/Stenosis undergoing primary decompressions/fusions resulted in lower LSC recurrence rates vs. for those having decompressions alone [Table 1]. [1,7,9,14,16] 1]. [4] Notably, preoperative LSC were located at the same level of DS (42.5%), and this correlated with facet arthropathy (89.3%), and degenerative disc disease (48.8%).…”
Section: Lsc/lumbar Stenosis Treated With Primary Decompressions/fusi...mentioning
confidence: 99%
“…[1] When Gonzalez et al (2023) evaluated 1631 patients with LSC undergoing primary laminectomy/instrumented fusions vs. 2212 with LSC having initial laminectomies alone, they found the laminectomy/fusion group had a lower 1.7% incidence of postoperative LSC recurrences requiring additional surgery vs. a much higher 3.1% recurrence rate of LSC for those undergoing initial decompressiona alone [Table 1]. [9] Low Failure Rates for Incomplete Surgical Resection of Lumbar Synovial Cysts 1]. [15] Partial LSC resections were largely attributed to marked cyst/dural adhesions, where dissection was carried around the residual capsule to avoid/limit the risk of dural tears/cerebrospinal fluid fistulas.…”
Section: Lsc/lumbar Stenosis Treated With Primary Decompressions/fusi...mentioning
confidence: 99%
See 3 more Smart Citations